Study On Cardiac Autonomic Nerve Function Status by Heart Rate Variability in Patients with Gastro-esophageal Reflux Disease - Sukrana Mamataj; Mahin Motaleb; Sabrina Fahmida Azim; Mohammed Iqbal Hossain (Central Medical College Journal, 2024)
Background: Gastro-esophageal reflux disease (GERD) has been associated with autonomic nervous dysfunction along with reduced Heart Rate Variability. Objective: To observe cardiac autonomic nerve function status by heart rate variability analysis in patients with Gastro-esophageal reflux disease (GERD). Methods: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka from 1st January, 2017 to 31st December, 2017. For this, total 30 male and female diagnosed GERD patients from the Out Patient Department (OPD) of Gastroenterology, BSMMU aged 20-35 years were included in the study group. Total power Low Frequency power (LF) and High Frequency power (HF) of HRV parameters were recorded. Thirty ages, BMI matched healthy subject also included as control. For statistical analysis, unpaired t-test was done as applicable. Results: Total power Low Frequency power (LF) and High frequency power (HF) were significantly lower in GERD patients in comparison to that of healthy subjects. The total power is the indicator of variability of the total cardiac autonomic nerve activities. LF power has represents sympathetic modulation on the heart and HF power is a marker of parasympathetic nerve activity on heart. Conclusion: This study concluded that autonomic dysfunction occurs in GERD patients which are characterized by decreased sympathetic & parasympathetic activity. Central Medical College Journal Vol 7 No 2 July 2023 Page: 87-91